2022
DOI: 10.3390/agriculture12020258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bacillus subtilis XZ18-3 as a Biocontrol Agent against Rhizoctonia cerealis on Wheat

Abstract: Rhizoctonia cerealis is a major fungal pathogen of wheat that causes great yield losses in all wheat-growing regions of the world. The biocontrol agent Bacillus subtilis XZ18-3 was investigated for inhibiting R. cerealis growth in wheat. The results of the mycelial growth test showed that the sterile filtrate of B. subtilis XZ18-3 could significantly inhibit the mycelial growth of R. cerealis and cause swelling and rupture of the mycelium. Observation by transmission electron microscopy indicated that the ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…When the fermentation supernatants were exposed to light for more than 6 h, their antifungal activity gradually decreased. But the inhibition rate was greater than 57% without significant changes, which indicated that the CFS had a strong tolerance to light, which agreed with sterile filtrates treated with illuminated light, and were stable in their activity against the pathogen (Yi et al 2022a). Biological control for plant pathogens is associated with the synthesis of bioactive substances, such as active protein, HCN and hydrolytic enzymes, considered as traits defining biocontrol ability (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…When the fermentation supernatants were exposed to light for more than 6 h, their antifungal activity gradually decreased. But the inhibition rate was greater than 57% without significant changes, which indicated that the CFS had a strong tolerance to light, which agreed with sterile filtrates treated with illuminated light, and were stable in their activity against the pathogen (Yi et al 2022a). Biological control for plant pathogens is associated with the synthesis of bioactive substances, such as active protein, HCN and hydrolytic enzymes, considered as traits defining biocontrol ability (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 60%
“…Acidbase treatment: CFS were divided into 7 equal parts, and every part was adjusted the pH to 1, 3, 5, 7, 9, 11 and 13 with 1 mol/l HCl and 1 mol/l NaOH, respectively, and pH 7 treatment was set as control (Hasani et al 2018). Ultraviolet light treatment: CFS were divided into 10 equal parts and placed at a distance of 30 cm under a 20 W UV lamp for 15,30,45,60,75,90,105,120,135 and 150 min, respectively, and the untreated CFS were set as control (Zhao et al 2017); light treatment: CFS were divided into 7 equal parts and placed in the illumination incubator (4000 lx) for light irradiation with 0, 2, 4, 6, 8, 10 and 12 h (Yi et al 2022a). Each test was repeated three times.…”
Section: Tests For Stability Of Antifungal Activity Of Cfsmentioning
confidence: 99%
“…In contrast, several taxa were significantly negatively correlated with Fusarium wilt incidence, including Bacillus , Altererythrobacter , Cryptococcus , and Saprospiraceae . Some species of Bacillus are already used as biocontrol agents against a wide range of fungal pathogens, including Rhizoctonia cerealis , Botrytis cinerea , Penicillium digitatum , and P. italicum ( Chen et al, 2020 ; Samaras et al, 2021 ; Yi et al, 2022 ). BF-treated soil also displayed a high abundance of Altererythrobacter , which is consistent with previous studies showing stable proliferation of the Erythrobacter YH-07 strain (which belongs to Altererythrobacter) after soil inoculation ( Tang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 39 ] reported that the application of a consortium of PGPR strains could reduce the sweet pepper disease, with the improvement of fruit quality and soil properties. Bacillus subtilis XZ18-3 was developed into a wettable powder with a control efficacy of 88.28% against Rhizoctonia cerealis on wheat [ 40 ]. In this work, B. subtilis PTS-394 wettable powder has an excellent and stable biocontrol effect both in pot and field trials and is a potential biocontrol agent for controlling the pepper root rot.…”
Section: Discussionmentioning
confidence: 99%